The Perception Of Class VII Students On Classical Assistance Services At SMP Negeri 26 Padang - Intan Verly Syafitri; Yusri Yusri (Universitas Negeri Padang, 2021)
Ideally, classical counseling is carried out so that students are active, creative and enthusiastic in the learning process according to the demands of the 2013 curriculum. In fact, counseling teachers still provide services using the lecture method, so students go in and out of learning, lie down, talk to friends and others. From interviews with counseling teachers, counseling teachers often perceive the provision of classical services by students as boring and useless lectures, and many students are not interested in taking classical services. The purpose of this study was to see how